The Common European Framework of Reference: a reference for Slovene - Ferbežar, Ina (Linguistica (Ljubljana), 2014)
In recent years the experts at the Centre for Slovene as a Second/Foreign Language have been linking Slovene language coursebooks and examinations to the CEFR. This paper describes the complex process of aligning texts, tasks and examples of language production (the spoken and written production of examination participants). A number of questions arose during this process, including: how to align tasks where the rubrics are at a higher level than the accompanying activities and the expected task performance? How to define the minimally acceptable person, on the basis of which the cut-off score is determined in receptive skills? How to align tasks where the performance calls for the use of different language skills? A particular challenge is represented by the benchmarking of the written and spoken production of the speakers of languages closely related to Slovene who make up the great majority of test takers. The final result of the linking process is a new language programme for teaching/learning, testing and certifying Slovene as a second and foreign language.
Keywords: Cadre européen commun de référence pour les langues; CECRL; examens; izpiti; manuels de langue; SEJO; Skupni evropski jezikovni okvir; Slovene; slovenščina; slovenščina kot drugi/tuji jezik; učbeniki